Model of the understanding of the Nature of Physics, Pedagogical Content Knowledge and Achievement Motivation toward Student's Preferences of Physics among teachers in Oman - Al Saadi, Ghanim Dhiyab Ya'qoub (Tanjong Malim, 2024)
Model of the understanding of the Nature of Physics, Pedagogical Content Knowledge and Achievement Motivation toward Student's Preferences of Physics among teachers in Oman by Al Saadi, Ghanim Dhiyab Ya'qoub